2023
DOI: 10.1039/d3dt00112a
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale control and tri-element co-doping of 4.6 V LiCoO2 with excellent rate capability and long-cycling stability for lithium-ion batteries

Abstract: Nanosizing and tri-element co-doping synergistically enhance the electrochemical performance of LiCoO2 at high voltage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Myung et al demonstrated that Al-doped LiCoO 2 not only inhibits phase transition but also inhibits transition metal dissolution [ 25 ]. In addition, in multiple-element co-doping, the applied elements were found to synergistically improve the electrochemical characteristics of LiCoO 2 , including Mg-Cu [ 26 ], Al-La [ 27 ], Ca-P [ 17 ], Ti-Mg-Sb [ 7 ], and Al-Mg-Ti [ 13 , 28 ]. Liu et al demonstrated that the double-doping of LiCoO 2 with Ca-P mitigated LiCoO 2 irreversible structural transformation, largely enhancing both cycling stability and rate performance [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Myung et al demonstrated that Al-doped LiCoO 2 not only inhibits phase transition but also inhibits transition metal dissolution [ 25 ]. In addition, in multiple-element co-doping, the applied elements were found to synergistically improve the electrochemical characteristics of LiCoO 2 , including Mg-Cu [ 26 ], Al-La [ 27 ], Ca-P [ 17 ], Ti-Mg-Sb [ 7 ], and Al-Mg-Ti [ 13 , 28 ]. Liu et al demonstrated that the double-doping of LiCoO 2 with Ca-P mitigated LiCoO 2 irreversible structural transformation, largely enhancing both cycling stability and rate performance [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Many studies have aimed to facilitate the performance of capacitance, but their long-cycle performance and capacity retention ability are still inferior. [3][4][5][6][7] In commercial LIBs, the most widely used anode materials, represented by graphite anodes, greatly restricted the time of endurance and performance for electronic devices powered by LIBs as a result of their restricted theoretical specific capacity (372 mA h g −1 ). 8,9 Instead, Fe 2 O 3 is a kind of outstanding lithium storage material owing to its low cost, availability, thermal stability, environmental friendliness, and superior theoretical specific capacity (1007 mA h g −1 ).…”
Section: Introductionmentioning
confidence: 99%